Motivations of tourists in wine regions: the case of La Rioja, Spain. Issue 3 (19th December 2019) - Vorobiova, Natalia; Pinto, Patrícia; Pintassilgo, Pedro; Lavandoski, Joice
Abstract : Purpose: This paper addresses the motivations of tourists who visit the region of La Rioja, Spain, which is well known for its internationally recognized, high-quality wines, yet remains understudied as a wine tourism destination. The paper aims to ascertain whether tourists are attracted to La Rioja because of its famous wines and wine-related activities or if other motivations exist. Design/methodology/approach: The data were derived from 217 questionnaires regarding tourists' motivations. A tourist survey was applied in La Rioja's capital city, Logroño, and segmentation analysis was undertaken. The data were first grouped into five factors regarding motivations for one's visit. These factors were then used to create two clusters: "wine tourists" and "other tourists". Findings: The results enabled us to detect different segments of tourists. The existence of two clusters suggests that tourists are motivated to visit the region for various reasons that are not necessarily wine-related. Thus, the region should be marketed to tourists beyond the theme of wine, as there is a demand for diverse experiences. Originality/value: Using the push and pull theory, this study contributes to the literature on the profile of visitors to wine tourism destinations by identifying differences in terms of motivations and other personal characteristics between "wine tourists" and the "other tourists". It also adds to the few existing studies on wine tourism segmentation in Spain through its focus on La Rioja, which is one of the most famous Spanish wine tourism destinations.